Social infrastructure: A viable opportunity for mitigating mental health crisis. Issue 2 (2nd July 2020) - Khetrapal, Neha; Agarwal, Sonal
ABSTRACT: Socially embedded patterns of interdependence confer community-level resilience and empower members by helping them to achieve shared goals during turbulent times. However, the current times have compounded adjustment problems for migrants who leave behind their social ties. To build psychological resilience at the community level, societies should tap into the latent power of social ties that assist all involved to discover a niche meaning for social cohesiveness. Despite the importance of economic and political infrastructure, leaders are looking for language-neutral social ecological tools that would allow migrants to reestablish social bonds in different cultural contexts and ensure their wellbeing. Examples are pulled from history and the contemporary times to explain how music lends itself as a candidate here. By allowing people to engage in distant but reciprocal music-making episodes, music-based community programs can play an important role in supporting the integration of migrant workers and mitigating mental health problems.